Do mobile health (mHealth) services ensure the quality of health life? An integrated approach from a developing country context. Issue 2 (17th February 2022) - Alam, Mohammad Zahedul; Alam, Mirza Mohammad Didarul; Uddin, Md. Aslam; Mohd Noor, Nor Azila
ABSTRACT: Though the acceptance behavior of health technology has been investigated by several studies from different theoretical perspectives, a unified understanding is still lacking in the literature particularly addressing the Generation Y (Gen Y). Thus, the current study aims to explore the factors affecting the adoption of mHealth services among Gen Yers and how does mHealth adoption influence their quality of health life along with trust and satisfaction. With this intention, the conceptual framework was developed integrating UTAUT2 and D&M IS Success Models to predict the mHealth adoption and consequently trust, satisfaction, and quality of health life. Data were collected from existing mHealth users in Bangladesh. Results demonstrate that performance expectancy, effort expectancy, facilitating condition, social influence, hedonic motivation, system quality, and services quality had a significant impact on mHealth adoption which in turn leads to building trust, satisfaction, and improve quality of health life. Research implications are also provided for the mHealth services providers, top marketing communication managers, and policymakers in formulating and implementing effective marketing strategies to increase the acceptability of mHealth.